The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pola.24756
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of pyrene end‐capped A6 dendrimer and star polymer with phosphazene core via “click chemistry”

Abstract: Novel hexa‐armed and pyrene (Pyr) end‐capped phosphazene dendrimer [N3P3‐(Pyr)6] and star polymer with poly(ε‐caprolactone) (PCL) arms [N3P3‐(PCL‐Pyr)6] were prepared via two series of reactions. In these series, core‐first approach was used starting from a hexa‐hydroxy functional phosphazene derivative (N3P3‐(OH)6). It was used as an initiator in the ring‐opening polymerization of ε‐caprolactone to prepare a hexa‐armed PCL star polymer (N3P3‐(PCL‐OH)6). Hydroxyl functionalities of N3P3‐(OH)6 and N3P3‐(PCL‐OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 100 publications
1
33
0
Order By: Relevance
“…29 He and coworkers reported that dansyl-functional aminoquinoline derivative can be employed in ratiometric detection of Zn(II) cation. 32,33 They have less entanglement in the solid state, high solubility in various organic solvents, as well as lower solution and bulk viscosities compared to linear ones having similar molecular weights. 31 Star-shaped polymers having multiple arms joined at the central core have attracted the attention of scientists due to their unique shape and possible processing advantages resulting from their compact structure.…”
Section: And Zhongmentioning
confidence: 99%
“…29 He and coworkers reported that dansyl-functional aminoquinoline derivative can be employed in ratiometric detection of Zn(II) cation. 32,33 They have less entanglement in the solid state, high solubility in various organic solvents, as well as lower solution and bulk viscosities compared to linear ones having similar molecular weights. 31 Star-shaped polymers having multiple arms joined at the central core have attracted the attention of scientists due to their unique shape and possible processing advantages resulting from their compact structure.…”
Section: And Zhongmentioning
confidence: 99%
“…Click chemistry method was selected due to its versatility, reliability, and specificity even in heterogeneous reaction systems . Moreover, it hardly requires protection of functional groups, gives high reaction yields, and has exclusive selectivity for the 1,4‐triazole formation …”
Section: Resultsmentioning
confidence: 99%
“…Pyrene‐containing macromolecular structures have attracted a great deal of attention to be employed in fluorescent probes due to their long fluorescence lifetime and a well‐defined fluorescence spectrum, which is sensitive to the polarity of the environment . There are numerous studies in the literature on the fluorescence sensor applications of pyrene‐containing molecular compounds and high‐molecular polymers toward various analytes, including nitroaromatic compounds, metal ions, anions, and glucose …”
Section: Introductionmentioning
confidence: 99%
“…When BR^is the halogen, it can be replaced with ease by alkoxy, aryloxy or amino groups via nucleophilic substitution reactions [1][2][3][4][5][6]. Hexachlorocyclotriphosphazene, trimer, N 3 P 3 Cl 6 , (1) or octachlorocyclotetraphosphazene, tetramer, N 4 P 4 Cl 8 (2) namely cyclophosphazenes are a kind of phosphazene compounds that they show many special characteristics.…”
Section: Introductionmentioning
confidence: 99%